Building infrastructure through PPP model: Policy lessons from RGIA - Viswanath, A.; Kumar, C. Jeevan (2008)
The Public Private Partnership (PPP) model in vogue in India is a policy outcome of a liberalised business environment. Aimed at encouraging private participation and partnership in augmenting infrastructure - especially in the aviation sector, it broadly lays emphasis on associating experienced business groups in this vital field. the experience shows that the Indian policy-makers welcomed the arrangement and facilitated policy implementation which resulted in construction of airports at Bengaluru, Hyderabad, Mumbai and Delhi. Crucial aspects are Concession Agreement with Government of India and state agreement with Government of Andhra Pradesh. New Concepts of Public Management like risk allocation to different partners - the GMR; the Airports Authority of India, the Government of India, the state government, the compulsion on the part of different partners to complete the assigned tasks within the timelines offers a challenge to theoreticians of New Public Management (NPM) and practicing administrators about the need for adoption of new methodological tools to assess the impact of such arrangements. The new airport that was build under PPP vastly improved the infrastructure in the aviation field. - Reproduced.
Keywords: Public private partnership